Complete Sternal Cleft Repair - Harijee, Ankita; Vijayaraghavan, Sundeep; Marathi, Arjun Reddy; Kottayil, Brijesh Parayaru; Kappanayil, Mahesh; Bayya, Praveen Reddy; Jayashankar, Jessin P (Indian Journal of Plastic Surgery, 2020)
Sternal cleft (SC) is a rare congenital malformation which can be partial or complete.We report a case of complete SC in a 9-month-old child. Our technique involves a combination of reinforcement with the deep cervical fascial extension, followed by the anterior perichondrial flaps, bridged with the rib graft, incorporating surplus resected cartilaginous xiphoid process, and covered with the bilateral pectoralis major muscle flap for the chest wall reconstruction with 3D printing assisting preoperative planning. The size of the defect in relation to the age of presentation was a deciding factor in the adoption of this alternative surgical technique.
Keywords: 3D printing; chest wall reconstruction; sternal cleft